2014
DOI: 10.1371/journal.pone.0097166
|View full text |Cite
|
Sign up to set email alerts
|

The Geometry and Dynamics of Lifelogs: Discovering the Organizational Principles of Human Experience

Abstract: A correlation dimension analysis of people’s visual experiential streams captured by a smartphone shows that visual experience is two-scaled with a smaller dimension at shorter length scales than at longer length scales. The bend between the two scales is a phase transition point where the lower scale primarily captures relationships within the same context and the higher dimensional scale captures relationships between different contexts. The dimensionality estimates are confirmed using Takens’ delay embeddin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(55 citation statements)
references
References 19 publications
4
51
0
Order By: Relevance
“…This gap is propagated through the rest of the results as a relative lack of image pairs that are multiples of ∼15 h apart. In prior work, we analyzed the structure of lifelogged images and demonstrated that image pairs taken from identical spatiotemporal locations occupied a lower dimensional manifold than those image pairs taken from separate spatiotemporal locations (19). By removing image pairs separated by less than 100 m and 15.6 h, we reduced the possibility that the images themselves would give rise to the present results as a consequence of within-and between-episode image properties.…”
Section: Methodsmentioning
confidence: 81%
See 2 more Smart Citations
“…This gap is propagated through the rest of the results as a relative lack of image pairs that are multiples of ∼15 h apart. In prior work, we analyzed the structure of lifelogged images and demonstrated that image pairs taken from identical spatiotemporal locations occupied a lower dimensional manifold than those image pairs taken from separate spatiotemporal locations (19). By removing image pairs separated by less than 100 m and 15.6 h, we reduced the possibility that the images themselves would give rise to the present results as a consequence of within-and between-episode image properties.…”
Section: Methodsmentioning
confidence: 81%
“…S1) with our custom lifelogging software that captured images along with their global positioning system (GPS) coordinates and timestamps (19). We collected an average of 5,414 ± 578 SEM images per subject, primarily from the Columbus, Ohio metropolitan area (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Natural signals contain potentially useful information over a wide range of temporal scales (e.g., Alvarez-Lacalle, Dorow, Eckmann, & Moses, 2006;Sreekumar, Dennis, Doxas, Zhuang, & Belkin, 2014;Voss & Clarke, 1975). Mathematical scaleinvariance, the property that memory does not have a characteristic scale, has been argued to be a central principle of cognitive psychology (Anderson & Schooler, 1991;Chater & Brown, 2008;Kello et al, 2010) and is a key feature of many behavioral models of timing, conditioning and episodic memory (Brown et al, 2000(Brown et al, , 2007Gallistel & Gibbon, 2000;Gibbon, 1977;Miall, 1989).…”
Section: The Representation Of History Is Scale-invariantmentioning
confidence: 99%
“…The fact that nearby neurons exhibit similarly sized place fields (Jung et al 1994;Kjelstrup et al 2008) suggests that there is a characteristic segment size for a species that moves through space at a particular rate. It is possible that salient events tend to happen at regular temporal or spatial intervals (Sreekumar et al 2014). Alternatively, the segment size may depend upon internal limitations of hippocampal processing, for example, the limited amount of time in which information can be held across a delay or a limited amount of time a cell can fire at a faster rate than the overall population (Geisler et al 2010).…”
Section: Theta Sequences Code For Behaviorally Relevant Spatial Segmentsmentioning
confidence: 99%